Passive-performance, analysis, and upgrades of a 1-ton seismic attenuation system. (20th February 2017) - Bergmann, G; Mow-Lowry, C M; Adya, V B; Bertolini, A; Hanke, M M; Kirchhoff, R; Köhlenbeck, S M; Kühn, G; Oppermann, P; Wanner, A; Westphal, T; Wöhler, J; et al.
Abstract: The 10 m prototype facility at the Albert–Einstein-institute (AEI) in Hanover, Germany, employs three large seismic attenuation systems to reduce mechanical motion. The AEI seismic-attenuation-system (AEI-SAS) uses mechanical anti-springs in order to achieve resonance frequencies below 0.5 Hz. This system provides passive isolation from ground motion by a factor of about 400 in the horizontal direction at 4 Hz and in the vertical direction at 9 Hz. The presented isolation performance is measured under vacuum conditions using a combination of commercial and custom-made inertial sensors. Detailed analysis of this performance led to the design and implementation of tuned dampers to mitigate the effect of the unavoidable higher order modes of the system. These dampers reduce RMS motion substantially in the frequency range between 10 and 100 Hz in 6 degrees of freedom. The results presented here demonstrate that the AEI-SAS provides substantial passive isolation at all the fundamental mirror-suspension resonances.